Pembentukan Karakter Anak Usia Dini Melalui Pengembangan Model Permainan Outbound Tumat Segar dan Tulang Kebo - Muliansyah, Adwianiro (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The aim of this research is to produce a product of outbond developing to the student ofNature School Baturaden year 2015.This research is developing research. To collect the datathe researcher use questionaire that we get from experts evaluation, questionaire for students,andalso by using the result of monitoring in field and the result of walk interview by thephysical exercise teacher. Data analyze technique that we use is descriptive percentage. Basedon the result of the research in small scale of the try out we get number 84,33 % ( good ), fromthe expert evaluation we get 79 %. The result of the try out in big scale we get 87,67 % ( good), the result of cognitive, afective and physcomotor aspects of the small try out and big tryout it increase with the difference 3,34 %. From the average of teacher’s questionaire and theheadmaster we get 86,67 % ( good ). Based on the catagory has been decide so the Tumat Segarand Tulang Kebo games is in good category. Based on the data we can take conclusion thatdeveloping outbond through Tumat Segar and Tulang Kebo games are effective in creatingcharachters of children of Nature School Baturaden